2007
DOI: 10.1080/10915810601163939
|View full text |Cite
|
Sign up to set email alerts
|

Final Report on the Safety Assessment of Capsicum Annuum Extract, Capsicum Annuum Fruit Extract, Capsicum Annuum Resin, Capsicum Annuum Fruit Powder, Capsicum Frutescens Fruit, Capsicum Frutescens Fruit Extract, Capsicum Frutescens Resin, and Capsaicin1

Abstract: Capsicum-derived ingredients function as skin-conditioning agents--miscellaneous, external analgesics, flavoring agents, or fragrance components in cosmetics. These ingredients are used in 19 cosmetic products at concentrations as high as 5%. Cosmetic-grade material may be extracted using hexane, ethanol, or vegetable oil and contain the full range of phytocompounds that are found in the Capsicum annuum or Capsicum frutescens plant (aka red chiles), including Capsaicin. Aflatoxin and N-nitroso compounds (N-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(17 citation statements)
references
References 322 publications
(316 reference statements)
2
15
0
Order By: Relevance
“…On the other hand, Lee and Park have reported an association between capsaicin at high doses with mutagenicity and carcinogenicity (Lee and Park 2003). Furthermore, several preclinical studies have suggested that the chili extract or capsaicin alone can have co-carcinogenic effects on the stomach, liver, colon and skin in different chemically-induced carcinogenesis models (Agrawal et al 1986;DĂ­az Barriga Arceo et al 1995;Johnson 2007;Liu et al 2015). Considering that the molecular mechanisms underlying the putative effects of capsaicin on colon carcinogenesis are largely unknown, this study aimed at assessing the effects of capsaicin oral administration on DNA damage, cell proliferation, and apoptosis, as well as on the expression of the genes involved in oxidative metabolism, antioxidant activity, cell cycle, DNA repair and cell death pathways during the early stages of colon carcinogenesis induced by 1,2-dimethylhydrazine (DMH) in rats.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Lee and Park have reported an association between capsaicin at high doses with mutagenicity and carcinogenicity (Lee and Park 2003). Furthermore, several preclinical studies have suggested that the chili extract or capsaicin alone can have co-carcinogenic effects on the stomach, liver, colon and skin in different chemically-induced carcinogenesis models (Agrawal et al 1986;DĂ­az Barriga Arceo et al 1995;Johnson 2007;Liu et al 2015). Considering that the molecular mechanisms underlying the putative effects of capsaicin on colon carcinogenesis are largely unknown, this study aimed at assessing the effects of capsaicin oral administration on DNA damage, cell proliferation, and apoptosis, as well as on the expression of the genes involved in oxidative metabolism, antioxidant activity, cell cycle, DNA repair and cell death pathways during the early stages of colon carcinogenesis induced by 1,2-dimethylhydrazine (DMH) in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies related capsaicin to weight loss in chronic feeding studies (Johnson, 2007;Lee, 1963). However, the 28-day study did not find that capsaicin nor other alkamides affect the daily consumption of standard food as reported (Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The actual percentage of capsaicin varies depending on the pepper source and method of extraction. 31 Therefore, in this study, we adopted semi-preparative HPLC method to get highly purified CAP product (purity >99%, Fig. 1B) to avoid potentially toxic impurities.…”
Section: Discussionmentioning
confidence: 99%